A new species of the genus Ishikawatrechus (Coleoptera, Trechinae) from Japan - Sugaya, Kazuki; Yamasako, Junsuke (Zootaxa, 2014)
A new species, Ishikawatrechus bidilatatus sp. nov., is described from the northwestern part of the Ishizuchi Range, Shikoku, Japan. The structure of the everted internal sac of the aedeagus in a fully inflated condition is observed and the taxonomic significance is discussed by comparing with a related species, I. ishiharai Uéno, 1994.